Using Grammatical Features for Automatic Register Identification in an Unrestricted Corpus of Documents from the Open Web. (9th January 2016) - Biber, Douglas; Egbert, Jesse
Abstract : Most previous attempts at automatic genre identification have been based on corpus samples that are relatively small and artificially restricted. In this study we set out to automatically predict register/genre categories in a large, representative sample of documents from the open web using a linguistic approach focused on lexico-grammatical characteristics that have functional associations. Our findings demonstrate the possibility of automatically predicting register/genre on the unrestricted open web, and we anticipate that future extensions will allow this task to be accomplished with considerably higher degrees of accuracy.